Efficacy of Fluoroscopically Guided Corticosteroid Injections for Foot and Ankle Pain. Issue 1 (January 2022) - Slone, Tyler; Ciesa, Michael; Bartholomew, Ania; Cheney, Nicholas A; Clark, Brian C.
Category: Midfoot/Forefoot; Ankle; Ankle Arthritis; Hindfoot; Lesser Toes Introduction/Purpose: Arthritis of the foot and ankle can severely hamper quality of life resulting in decreased mobility and functionality. Conservative treatment can involve corticosteroid injections into affected joint spaces. Fluoroscopic guided injections provide confirmation that the injection was successfully applied within the appropriate joint space. Due to this, they can be of diagnostic value and result in more accurate injection placement. Current literature focuses on ultrasound guided injections and does not fully address the efficacy of fluoroscopic injections. Objective: Assess and determine overall efficacy of fluoroscopically guided corticosteroid injections including the degree and period of relief provided. Methods: We retrospectively reviewed patient charts from 2016 through 2020 of patients that received fluoroscopically guided corticosteroid injections in foot or ankle joints. 224 injections were reviewed, gathering responses to percent relief, days of relief, pre-/post-injection VAS pain score and efficacy of repeat injections. Additionally, Kellgren-Lawrence arthritis scale vs pain relief were analyzed. Results: Analysis limited by incomplete patient response. 24/83 (28.9%) injections provided less than 2 weeks of relief while 59/83 (71.1%) injections averaged 109.49 +- 72.03 days of pain relief. Of 127 responses, post-injection relief at first follow up had an average VAS reduction of 2.87 +- 3.17 with 70.38 +- 30.8 % improvement. 40 subjects with repeat injections had 109.41 +- 64.96 days of relief per injection. No significant correlation was found between joint injected or degree of arthritis and percent improvement. Conclusion: Fluoroscopic guided injections are an effective conservative option providing prolonged but varying relief of 3-4 months irrespective of the specific joint or degree of arthritis. Repeat injections show similar efficacy. In contrast to ultrasound guided injections, fluoroscopy provides additional diagnostic and therapeutic value. This can be beneficial if the injections fail and the patient must progress to surgery. Future prospective studies could directly compare different injections modalities and further analyze efficacy for specific diagnoses.